2008
DOI: 10.1002/bsl.825
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic profiles of offenders in substance abuse treatment programs

Abstract: This study examined the association of Axis I and Axis II disorders among offenders who were in prison-based substance abuse treatment in a national multi-site study. Participants (N = 280) received a psychosocial assessment and a structured diagnostic interview in two separate sessions. Logistic regression models examined the association between lifetime mood and anxiety disorders with two personality disorders, and the relationship of Axis I and Axis II disorders (alone and in combination) to pre-treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Substance use, abuse and dependence among individuals with ASDP is relatively common, a fact that may corroborate the findings here [22,23]. This was seen in a number of studies that analysed samples from substance users whose levels of correlation with antisocial personality disorder varied from 20% to 68% [24]. The wide variation seems to be in function of the nature of the samples, most of which were comprised in prison inmates.…”
Section: Discussionsupporting
confidence: 84%
“…Substance use, abuse and dependence among individuals with ASDP is relatively common, a fact that may corroborate the findings here [22,23]. This was seen in a number of studies that analysed samples from substance users whose levels of correlation with antisocial personality disorder varied from 20% to 68% [24]. The wide variation seems to be in function of the nature of the samples, most of which were comprised in prison inmates.…”
Section: Discussionsupporting
confidence: 84%
“…Notably 80% of inmates with substance use disorders had a comorbid psychiatric disorder; most commonly anxiety disorders and personality disorders. There are few data on comorbidity in men in prison; however, high rates of comorbid disorders have been reported among prisoners with substance use disorders in studies of those with identified mental health needs (Berto, Tartari, Tabacchi, Gerra, & Tamburino, 2005;Chiles, Von Cleve, Jemelka, & Trupin, 1990;Grella, Greenwell, Prendergast, Sacks, & Melnick, 2008;National Gains Center, 1997;Palijan, Muzinić, & Radeljak, 2009;Peters & Hills, 1993).…”
Section: Discussionmentioning
confidence: 94%
“…Henderson, 1998). The presence of co-occurring disorders has significant implications for reentry as both conditions (i.e., substance abuse and psychiatric disorders) have been linked to higher recidivism and relapse rates (Grella, Greenwell, Prendergast, Sacks, & Melnick, 2008;McNiel, Binder, & Robinson, 2005). Prior research has also shown that offenders with co-occurring disorders have worse treatment outcomes than those with a single disorder (Messina, Burdon, Hagopian, & Prendergast, 2006).…”
Section: Female Criminality and Drug Usementioning
confidence: 97%